Submesoscale Fronts in the Antarctic Marginal Ice Zone and Their Response to Wind Forcing - Swart, Sebastiaan; du Plessis, Marcel D.; Thompson, Andrew F.; Biddle, Louise C.; Giddy, Isabelle; Linders, Torsten; Mohrmann, Martin; Nicholson, Sarahâ€Anne (Geophysical Research Letters, 2020)
Submesoscale flows in the ocean are energetic motions, O(1â€“10 km), that influence stratification and the distributions of properties, such as heat and carbon. They are believed to play an important role in seaâ€iceâ€impacted oceans by modulating airâ€seaâ€ice fluxes and seaâ€ice extent. The intensity of these flows and their response to wind forcing are unobserved in the seaâ€ice regions of the Southern Ocean. We present the first submesoscaleâ€resolving observations in the Antarctic marginal ice zone (MIZ) collected by surface and underwater autonomous vehicles, for >3 months in austral summer. We observe salinityâ€dominated lateral density fronts occurring at subâ€kilometer scales. Surface winds are shown to modify the magnitude of the mixedâ€layer density fronts, revealing strongly coupled atmosphereâ€ocean processes. We posture that these windâ€front interactions occur as a continuous interplay between front slumping and vertical mixing, which leads to the dispersion of submesoscale fronts. Such processes are expected to be ubiquitous in the Southern Ocean MIZ. Â© 2020 The Authors. This is an open access article under the terms of the Creative Commons Attributionâ€NonCommercialâ€NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is nonâ€commercial and no modifications or adaptations are made. Received 13 DEC 2019; Accepted 2 MAR 2020; Accepted article online 4 MAR 2020. This work was supported by the following grants: Wallenberg Academy Fellowship (WAF 2015.0186), Swedish Research Council (VR 2019â€04400), STINTâ€NRF Mobility Grant and NRFâ€SANAP (SNA170522231782), and AFT was supported by the Terrestrial Hazard Observations and Reporting (THOR) and ONR (N00014â€19â€1â€2421). We thank Sea Technology Services (STS), SANAP, the captain and crew of the S.A. Agulhas II for their fieldâ€work/technical assistance. We thank David Peddie of Offshore Sensing AS for assistance with the Sailbuoy. S.S. is grateful to Geoff Shilling and Craig ...